External Determinants of Learning Motivation among Vietnamese Pedagogical Students: Evidence from PLS-SEM - Hoang Thi Thinh; Nguyen Thi Thanh Tung (CV FOUNDAE, 2026)
In the context of significant transformations in Vietnamese higher education (VHE) under the impact of digital transformation and educational reform, identifying the factors influencing learning motivation (LM) of Vietnamese Pedagogical Students (VPSs) is becoming increasingly urgent. Based on the integration of theoretical approaches and recent studies on LM, and considering the cultural and educational context of Vietnam, this study aims to examine the extent and differences in the influence of external factors on VPSs’ LM. Four factors were proposed: (1) the role of lecturers, (2) institutional support, (3) infrastructure, technology, and learning resources, and (4) family and community encouragement. This study employed a quantitative survey design involving 587 students from two public teacher training universities in Vietnam. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The results indicate that all four factors have a positive impact on LM, with lecturer role showing the strongest influence (β = 0.429), followed by institutional support (β = 0.270), infrastructure and resources (β = 0.148), and family support (β = 0.091). These findings provide contextual evidence on how external conditions shape LM and offer policy implications for improving teacher education quality through strengthening pedagogy, digital capacity, and equitable access to learning resources.